2011
DOI: 10.1109/tuffc.2011.1959
|View full text |Cite
|
Sign up to set email alerts
|

Development and characterization of a tissue-mimicking material for high-intensity focused ultrasound

Abstract: A tissue-mimicking material (TMM) for the acoustic and thermal characterization of high-intensity focused ultrasound (HIFU) devices has been developed. The material is a high-temperature hydrogel matrix (gellan gum) combined with different sizes of aluminum oxide particles and other chemicals. The ultrasonic properties (attenuation coefficient, speed of sound, acoustical impedance, and the thermal conductivity and diffusivity) were characterized as a function of temperature from 20 to 70°C. The backscatter coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(79 citation statements)
references
References 30 publications
1
78
0
Order By: Relevance
“…Phase change due to displacement was separated from that due to temperature by complex subtraction of an interleaved volume acquired with no FUS applied. Temperature was obtained using the proton resonance frequency method with a referenceless background phase subtraction [6]. Experiments were performed in a gelatin phantom and excised pig brain on 3 T MRI scanners (Siemens Tim Trio and PrismaFit).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phase change due to displacement was separated from that due to temperature by complex subtraction of an interleaved volume acquired with no FUS applied. Temperature was obtained using the proton resonance frequency method with a referenceless background phase subtraction [6]. Experiments were performed in a gelatin phantom and excised pig brain on 3 T MRI scanners (Siemens Tim Trio and PrismaFit).…”
Section: Resultsmentioning
confidence: 99%
“…For each cycle, six in total, patients will receive a combination of ThermoDox and HIFU-induced hyperthermia followed by cyclophosphamide. All MR-HIFU experiments will be performed on a dedicated breast MR-HIFU system (Philips Healthcare, Vantaa, Finland) integrated with a clinical 1.5 T MRI scanner (Achieva, Philips Healthcare, Best, The Netherlands) [6,7]. Four to six weeks after finishing the last cycle of chemotherapy the patients will undergo surgery.…”
Section: A133mentioning
confidence: 99%
See 1 more Smart Citation
“…[26][27][28][29] TMM phantoms bridge the gap in translational research without the need of direct experimentation on humans or animals. The phantoms designed with TMMS are essential for assessing different technologies, and for training and research.…”
Section: Introductionmentioning
confidence: 99%
“…Various kinds of TMMs have already been used in ultrasound research, such as gelatine, agar, silicone, and polyacrylamide (PAA) gel. [26][27][28][29] The key parameters in material characterization for ultrasound imaging include the acoustic velocity, the acoustic impedance, and the acoustical attenuation, while Young's modulus is an important parameter for elastography phantoms. Madsen et al 30 have demonstrated the use of TM phantoms for standardization of both ultrasound imaging of the prostate 26 and for elastographic imaging 18, 31 using agar and gelatine materials.…”
Section: Introductionmentioning
confidence: 99%